An in situ electrochemical impedance spectroscopy/synchrotron radiation grazing incidence X-ray diffraction study of the influence of acetate on the carbon dioxide corrosion of mild steel - De Marco, Roland; JIang, Zhong-tao; John, Doug; Sercombe, Matthew; Kinsella, Brian (Pergamon-Elsevier Science Ltd, 2007)
A combination of electrochemical impedance spectroscopy (EIS) and in situ synchrotron radiation grazing incidence X-ray diffraction (SRGIXRD) has been used to study the influence of acetate on the carbon dioxide corrosion of mild steel. The SR-GIXRD data demonstrated that normal corrosion - in a carbon dioxide saturated brine - induced the formation of a thick corrosion scale of Fe2(OH)2CO3 and Fe2O2CO3, and this totally obscured the -Fe diffraction peaks of the underlying steel substrate after 24 h. On the other hand, the carbon dioxide corrosion of mild steel in the presence of acetate also detected the Bragg diffraction peaks for Fe2(OH)2CO3 and Fe2O2CO3; however, the -Fe diffraction peaks of the underlying steel substrate were not extinguished with time, and there was a reversal in the pattern of evolution of the intensities of the Fe2(OH)2CO3 and Fe2O2CO3 phases in acetate. Accordingly, the EIS data showed a poorly defined medium frequency time constant for the corroded steel specimen in brine spiked with acetate, and this medium frequency time constant was extinguished as a function of time. Alternatively, EIS of the corroded specimen also revealed a medium frequency time constant after 24 h. In addition, EIS complex?plane impedance plots showed that the corroded electrode had become passivated in an acetate-spiked brine, as evidenced by a three-fold enhancement in the charge transfer resistance at low frequency. These EIS/SR-GIXRD outcomes suggest that acetate affects the crystallization chemistry of the Fe2(OH)2CO3/Fe2O2CO3 corrosion scale, and this causes a mild passivation of the corroded steel surface.